IMPLEMENTATION OF MARKETING MIX STRATEGY IN ATTRACTING PATIENTS' INTEREST IN TREATMENT AT MAYJEN HM RYACUDU REGIONAL HOSPITAL, BUMI CITY, NORTH LAMPUNG REGENCY - Finny Redjeki; Etty Sofia Mariati Asnar; Yuana Cita Adhyaksa Putri; Vip Paramarta; Ayu Laili Rahmiyati; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The decline in outpatient visits is a major challenge for regional hospitals amidst increasing competition in healthcare services. This study aims to analyze the implementation of the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) in increasing outpatient visits at Mayjen HM Ryacudu Regional General Hospital in Kotabumi, Lampung. The study used a qualitative approach with a case study method. Data were collected through in-depth interviews with management, medical personnel, and patients, which were then validated through source triangulation, field observation, and documentation. Then, they were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that price and place elements are the hospital's main strengths due to affordable rates and strategic location. However, limited pricing flexibility due to government regulations limits the function of price as a differentiation tool. People and process elements play a significant role in shaping patient perceptions of service quality, while promotion has not been optimally utilized. A SWOT analysis places the hospital in a position that requires aggressive market penetration through service digitalization and physical facility modernization to restore public trust and increase visits by BPJS and general patients. This study emphasizes the importance of integrating all elements of the 7P marketing mix synergistically to increase patient interest in visiting regional hospitals.